THE DICTIONARY OF REGIONAL ONOMASTICS AS A RESOURCE OF DEVELOPMENT OF PRIMARY SCHOOL CHILDREN’S LINGUISTIC AND REGIONAL KNOWLEDGE - Rogaleva, Elena; Nikitina, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article summarizes the experience of developing primary school children’s linguistic and regional knowledge by means of a dictionary of regional onomastics created by the specialists of the Experimental Laboratory of Educational Lexicography of Pskov State University. It presents the author’s concept of a dictionary called “The Streets of My Home Town”. It contains the examples of dictionary entries and lessons based on the materials of the dictionary and intended for primary school children. The author describes the levels of acquisition of linguistic and regional knowledge for primary school children.